(untitled) (E Conference Zone, 2024)
It is known that active forms of oxygen in the body maintain cell homeostasis and participate in oxidation-reduction processes, while excess production has a destructive effect on the cell and its structures. As a result, a number of pathological conditions arise. The development of free-radical processes in human tissue cells by many endogenous and exogenous pathways causes extensive oxidative damage, leading to various human diseases [1]. Therefore, the search for and study of regulators of free-radical processes based on biologically active compounds of plant origin remains relevant. In this regard, polyphenolic compounds are of particular interest, since they have long established themselves as powerful antioxidants [2]. As is known, polyphenolic compounds are an inexhaustible source of drugs with various therapeutic effects [3].